Protective Effects of α-Tocopherol and Ascorbic Acid against Cardol-Induced Cell Death and Reactive Oxygen Species Generation in Staphylococcus aureus - Murata, Wakae; Tanaka, Toshio; Kubo, Isao; Fujita, Ken-ichi (Planta Medica, 2013)
Cardol (C15 : 3), isolated from cashew (Anacardium occidentale L.) nut shell liquid, has been shown to exhibit bactericidal activity against various strains of Staphylococcus aureus, including methicillin-resistant strains. The maximum level of reactive oxygen species generation was detected at around the minimum bactericidal concentration of cardol, while reactive oxygen species production drastically decreased at doses above the minimum bactericidal concentration. The primary response for bactericidal activity around the bactericidal concentration was noted to primarily originate from oxidative stress such as intracellular reactive oxygen species generation. High doses of cardol (C15 : 3) were shown to induce leakage of K+ from S. aureus cells, which may be related to the decrease in reactive oxygen species. Antioxidants such as α-tocopherol and ascorbic acid restricted reactive oxygen species generation and restored cellular damage induced by the lipid. Cardol (C15 : 3) overdose probably disrupts the native membrane-associated function as it acts as a surfactant. The maximum antibacterial activity of cardols against S. aureus depends on their log P values (partition coefficient in octanol/water) and is related to their similarity to those of anacardic acids isolated from the same source.
Keywords: bactericidal effect; cardol; methicillin-resistant Staphylococcus aureus; membrane injury; reactive oxygen species